Application-Based Flipbook Increases Student Learning Motivation: Flipbook Berbasis Aplikasi Meningkatkan Motivasi Belajar Siswa - Ghifari, Muhammad Zaky; Linggowati, Tri (Indonesian Journal of Education Methods Development, 2024)
General Background: Effective learning media is crucial for fostering student engagement and understanding, particularly in mathematics education. Specific Background: However, teachers often lack variety in their instructional materials, leading to decreased student enthusiasm and challenges in grasping mathematical concepts. Knowledge Gap: Existing research has not sufficiently addressed the development and implementation of innovative digital media, such as flipbooks, in primary mathematics education. Aims: This study aims to improve the quality of application-based digital flipbook media for fourth-grade mathematics, focusing on recognizing flat shapes and understanding their area formulas. Results: Employing a research and development (R&D) methodology consisting of five stages—analysis, design, development, implementation, and evaluation—data were collected through questionnaires assessed by material experts, media experts, and educators. The validation results showed that media expert ratings were 93.75% and 85%, while material experts scored 90% and 80%, all categorized as "very feasible." Student feedback during a large group test yielded an 86.2% feasibility rating. Novelty: This study contributes to the field by presenting a validated digital flipbook as a novel educational tool for mathematics instruction. Implications: The findings suggest that integrating application-based flipbooks into the mathematics curriculum can significantly enhance the learning experience and motivation of fourth-grade students, promoting a more engaging educational environment. Highlights: Improved Engagement: The application-based flipbook significantly increased student enthusiasm for mathematics. High Validation Ratings: Experts rated the digital flipbook as "very feasible," with scores above 85%. Structured Development Process: The study utilized a comprehensive R&D methodology to create the educational tool. Keywords: flipbook, application, mathematics, student engagement, educational media